Optimal E-Powertrain Solutions for Future Electric Vehicles - Erfan Mohagheghi; Joan Gubianes Gasso; Pu Li (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
Owing to increasing emission specification, decreasing price of energy storage systems and power electronic devices, in addition to fast-developing technology, Electric Vehicles  (EVs) will become a significant share of automotive market in the near future [1]. Therefore, there is a huge competition among car manufacturers to produce EVs. The final price and driving range are known as vital factors to win the competition.